1985
DOI: 10.1093/icb/25.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Nemertine Integument with Consideration of Its Ecological and Phylogenetic Significance

Abstract: SVNOPSIS. The phylum Nemertina, with more than 800 described species, occupies a wide range of habitats and figures prominently in theories of bilaterian evolution. Integuments of nemertines, from a number of habitats and representing the major orders, are compared and the general cell types constituting the epidermis are reviewed and defined. The general construction and cell demography of the integument are more or less characteristic for each order, but are not readily generalized to lower taxonomic levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 23 publications
5
53
0
Order By: Relevance
“…4) is 12-30 µm thick, but with few acidophilic gland cells in the ventral pre-cerebral regions of the head (Figs 4-7) compared with other regions of the body. Basally the epidermis possesses a distinct basal-cup zone, as described by Norenburg (1985). The dermis is only 1-7 µm thick but distinct (Fig.…”
Section: Descriptionmentioning
confidence: 83%
“…4) is 12-30 µm thick, but with few acidophilic gland cells in the ventral pre-cerebral regions of the head (Figs 4-7) compared with other regions of the body. Basally the epidermis possesses a distinct basal-cup zone, as described by Norenburg (1985). The dermis is only 1-7 µm thick but distinct (Fig.…”
Section: Descriptionmentioning
confidence: 83%
“…But this view has been questioned (e.g., Norenburg, 1985;Turbeville, 1991) and is not supported by alternative cladistic analyses of morphology (Eernisse et al, 1992;Schram, 1991;Zrzavy et al, 1998). The latter analyses suggest that the nemerteans are most closely related to spiralian (Protostome) coelomates.…”
Section: Outgroup Sequence Analysis and Phylogeny Reconstructionmentioning
confidence: 99%
“…Turbeville (1991) furthermore interprets the presence of unique secretory bodies (rhabdoids or pseudocnids) in palaeo-and heteronemerteans as a possible synapomorphy. Also, Norenburg (1985Norenburg ( , 1993 concluded that the palaeonemerteans form a nonmonophyletic group and that some palaeonemertean taxa (e.g., Hubrechtella) were more closely related to heteronemerteans than to other palaeonemerteans. We, however, have not been able to establish any well-supported sister group relationships between the palaeonemertean and the heteronemertean species included using 18S rDNA sequences.…”
mentioning
confidence: 99%
“…The defi nite, adult epidermis consists of multiciliated cells, several types of gland cells, basal granular cells, and basal neurites originating from subepidermal neurons constituting a pseudostratifi ed epithelium in paleonemertean and heteronemertean species (Turbeville 1991 ). In Hoplonemertea, due to the presence of a basal cup cell layer, the pseudostratifi ed appearance of the epidermis is even more pronounced (Norenburg 1985 ;Turbeville 1991 ). The heteronemertean dermis is formed late in development, i.e., after metamorphosis, by some gland cells sinking underneath the level of the ciliated epidermis cells.…”
Section: Epidermismentioning
confidence: 99%